"THE EFFECT OF MINERAL AND ORGANIC FERTILIZERS APPLIED TO SUNFLOWERS ON THEIR GROWTH, DEVELOPMENT, AND PRODUCTIVITY (UNDER THE SOIL AND CLIMATIC CONDITIONS OF THE FERGHANA REGION)" (Scientific journal of the Fergana State University, 2025)
Development and implementation of a scientifically based system of application timing and rates of mineral and organic fertilizers on the growth, development and productivity of plants when caring for sunflower varieties grown in the soil and climatic conditions of the Fergana region, to study the influence of the oil level in sunflower seeds with an emphasis on the use mineral fertilizers when growing sunflower.